The Global Food Crisis and its Impact on Nutritional Adequacy in Developing Countries - Mitra Mustika lubbis (Pt. Anagata Sembagi Education, 2024)
The global food crisis afflicting developing countries is further exacerbated by dependence on food imports, which makes these countries highly vulnerable to fluctuations in international food prices. This dependence limits the access of people, especially the poor, to nutritious food and hinders the development of local food production. Disparities in food distribution and climate change affecting agricultural yields also exacerbate food security problems. Malnutrition, especially among children and pregnant women, is widespread, threatening the quality of future generations. This study uses a qualitative approach with in-depth interviews and focus group discussions (FGDs) to explore the impact of the food crisis on nutritional adequacy in developing countries. The findings show that solutions that can reduce dependence on food imports include policies that support the diversification of local food production, strengthening the agricultural sector, and implementing agricultural technology adaptive to climate change. In addition, access to nutritious food and appropriate interventions for vulnerable groups are needed to address malnutrition. This research emphasizes the importance of equitable food distribution policies and adequate infrastructure to improve food security and the quality of life of people in developing countries